Pengaruh Penyuluhan Makanan Jajanan Dengan Metode Permainan Ular Tangga Terhadap Pengetahuan Anak Sekolah Di SDN 2 Kuta Kabupaten Lombok Tengah - Sarianti Sarianti; I Nyoman Adiyase; Susilo Wirawan; Yuli Laraeni (Poltekkes Kemenkes Mataram, 2019)
Background: Based on the results of basic health research (RISKESDAS) in 2013, in NTB in the age group 10 years and over, having a risky dietary consumption behavior is by consuming sweet foods 32.3%, salty 10.9%, fatty 26.1 %, burned 5.6%, animal preserved 4.4%, flavored 84.8%, coffee 37.5%, caffeine besides coffee 4.3% of their daily needs. Based on data from preliminary studies at SDN 2 Kuta, getting from 43 children as many as 41 children the knowledge of snack foods is in the less category, namely 95.3% and only 2 children from 43 children who have knowledge of snack foods are in the sufficient category of 4.7 %.Objective: To find out the influence of snack food counseling with the method of snake and ladder games on the knowledge of school children in class V students.Method: Using a quasy experimental non equivalent control group, with a sample of 22 people. Collecting knowledge data obtained from questionnaires, data is processed descriptively. Analysis using the independent T-test and paired t-test.Results: The results of this study indicate that street food counseling using the snake ladder method has a significant influence on the knowledge of school children (p value = <0.005)Conclusion: Extension of snack foods using the snake ladder method has an influence on the knowledge of school children at SDN 2 Kuta Central Lombok Regency.